Analysis the mechanical properties and material characterization on Magnesium Metal Matrix Nano composites through stir casting process. (2021) - Sathishkumar, P.; Deepakaravind, V.; Gopal, P.; Azhagiri, Pon
Abstract: The main objective for this work are explored and evaluate the feasibility of fabrication of Magnesium Metal matrix Nano composites (MMNCs) using Stir casting process. It has increasingly used becoming attractive materials in advanced industrial applications. Since it has high demands for energy saving as well as lightweight materials attract a large amount of research interest. Here Magnesium used as basic matrix composite in fabrication of MMNCs. Hence Magnesium as lightweight structural metal and high strength-to-weight ratio of alloys are usually a major reason for considering these materials in engineering designs as well as fabrication of composite material. This magnesium alloys are widely used in automotive, aerospace and chemical applications in wide scale that is because of their low density. However, their applications are quite restricted within their low strength and ductility. By addition of nano size reinforcements in the base matrix magnesium alloy, thus for giving them excellent properties are to be a hopeful choice for many applications as well as for improving their mechanical properties. In this paper aims to study the effect of reinforcement on the microstructure and mechanical properties like tensile strength, yield strength, ductility, strain and micro structure analysis of Magnesium metal matrix nano composite.